Myanmar Public Expenditure Review 2017 : Fiscal Space for Economic Growth - World Bank Group (World Bank, Yangon, 2017)
Myanmar had a strong economic take off between 2011 and 2015, but sustaining it will depend on improvements to public services and infrastructure. Yet general government spending at 15 percent of gross domestic product (GDP) is much lower than what is needed to deliver these improvements, and well below countries at a similar level of development that spend over 20 percent of GDP on public services. The first public expenditure review (PER) for Myanmar found that since the country opened up in 2011, it moved quickly to allocate considerably more resources to priority public services. Macroeconomic challenges in the past two years have contributed to deteriorating fiscal conditions. Part of these challenges are structural - Myanmar is dependent on commodity receipts, is prone to natural disasters, and has a narrow production base. These challenges are exacerbated by policy and institutional capacity constraints. Fiscal buffers are limited by low revenue (10 to 12 percent of GDP), with considerable economic activity in either hard-to-tax sectors or dominated by small and micro enterprises. On the potential for reallocating resources, the PER analyzes: (i) the allocative efficiency of capital expenditures, to identify options for reprioritizing spending to higher-valued use, and the productive efficiency of capital expenditures, to minimize waste in project implementation; and (ii) the fiscal impact of state economic enterprises (SEEs) to present a strategy for the government to maximize returns from and minimize subsidies to SEEs.